2000
DOI: 10.1016/s0022-5347(05)67104-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cytology and Fluorescence in Situ Hybridization for the Detection of Urothelial Carcinoma

Abstract: The sensitivity of FISH for the detection of urothelial carcinoma is superior to that of cytology, and the specificity of FISH and cytology for urothelial carcinoma are not significantly different. Further prospective studies are required but FISH has the potential to improve significantly the management of urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
155
1
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(171 citation statements)
references
References 41 publications
9
155
1
6
Order By: Relevance
“…22 Only sparse data are available in the literature regarding the use of FISH on endoscopic brush cytology specimens for biomarker assessment in Barrett's esophagus. Recently, a group of investigators from Denmark applied FISH to cell pellets obtained from endoscopic brushings, and analyzed the aneusomic states of chromosomes 4,8,20, and Y, as well as genomic losses of p16, p53, and retinoblastoma (Rb) gene loci. 44 This study showed that while aneusomy of chromosomes 4 and 8, and a p16 locus deletion are early changes present in the metaplastic Barrett's epithelium, p53 genomic loss (and rarely Rb loss) occurs predominantly in HGD and adenocarcinoma arising in Barrett's esophagus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Only sparse data are available in the literature regarding the use of FISH on endoscopic brush cytology specimens for biomarker assessment in Barrett's esophagus. Recently, a group of investigators from Denmark applied FISH to cell pellets obtained from endoscopic brushings, and analyzed the aneusomic states of chromosomes 4,8,20, and Y, as well as genomic losses of p16, p53, and retinoblastoma (Rb) gene loci. 44 This study showed that while aneusomy of chromosomes 4 and 8, and a p16 locus deletion are early changes present in the metaplastic Barrett's epithelium, p53 genomic loss (and rarely Rb loss) occurs predominantly in HGD and adenocarcinoma arising in Barrett's esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, abnormalities detectable by FISH may precede the evidence of carcinoma on bladder biopsies. 8,9 FISH has also shown promise in the detection of carcinomas of the breast, lung, and colon. [10][11][12][13] Multiple genetic abnormalities have been reported in Barrett's esophagus-associated adenocarcinoma and its precursors.…”
mentioning
confidence: 99%
“…7 The gold standard for diagnosis and surveillance of urothelial carcinoma has traditionally been cystoscopy and urine cytology, however both have limitations. [8][9][10][11][12][13][14] Although urine cytology is excellent for detecting high-grade urothelial carcinoma (sensitivity and specificity 475%), it has a low sensitivity (20-60%) for detecting low-grade tumors. 8,[10][11][12][13][14] The low sensitivity of urine cytology, the invasiveness of cystoscopy and its limited usefulness in detecting flat and inaccessible lesions have prompted increased demand for newer, more sensitive and non-invasive tests for detection of urothelial carcinoma.…”
mentioning
confidence: 99%
“…17,18 Urovysiont FISH has a reported sensitivity of 73-92%, a specificity of 89-96% for urothelial carcinoma detection and several studies have confirmed its usefulness in the diagnosis and surveillance of these tumors. 8,14,[19][20][21][22] The test is designed to detect aneuploidy for chromosomes 3, 7, 17, and loss of the 9p21 locus in malignant urothelial cells that are shed in the urine of persons with urothelial carcinoma. These represent some of the most common chromosomal abnormalities in urothelial carcinoma.…”
mentioning
confidence: 99%
“…Fluorescence in-situ hybridisation (FISH) of exfoliated bladder cells has been shown to have a greater sensitivity than conventional urine cytology in the detection of transitional cell carcinoma of the bladder (Halling et al, 2000). Possibly therefore, detection of early chromosomal changes indicative of genomic instability at the enterovesical anastomosis in patients who have undergone enterocystoplasty may identify those at high risk of tumorigenesis before a potentially fatal cancer has occurred.…”
mentioning
confidence: 99%